2006
DOI: 10.1161/01.res.0000207384.81818.d4
|View full text |Cite
|
Sign up to set email alerts
|

An In Vivo Analysis of Hematopoietic Stem Cell Potential

Abstract: Recent studies evaluating hematopoietic stem cell (HSC) potential raise the possibility that, in addition to embryonic sources, adult valve fibroblasts may be derived from HSCs. To test this hypothesis, we used methods that allow the potential of a single HSC to be evaluated in vivo. This was achieved by isolation and clonal expansion of single lineage-negative (Lin-), c-kit(+), Sca-1(+), CD34- cells from the bone marrow of mice that ubiquitously express enhanced green fluorescent protein (EGFP) combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(77 citation statements)
references
References 50 publications
4
72
0
1
Order By: Relevance
“…40 While some of the mechanisms involved in valve disease are similar to those in atherosclerosis, recent observations suggest anatomical, cellular, and genetic mechanisms that are unique to the aortic valve. 12,40,41 Accordingly, an improved understanding of the pathogenesis of calcific aortic valve disease requires better definition of these unique features, including the characteristics of the cell populations involved in the disease. In the present study, we identified for the first time a mesenchymal progenitor cell population in the aortic valve using rigorous quantitative assays established in the mesenchymal stem cell field.…”
Section: Discussionmentioning
confidence: 99%
“…40 While some of the mechanisms involved in valve disease are similar to those in atherosclerosis, recent observations suggest anatomical, cellular, and genetic mechanisms that are unique to the aortic valve. 12,40,41 Accordingly, an improved understanding of the pathogenesis of calcific aortic valve disease requires better definition of these unique features, including the characteristics of the cell populations involved in the disease. In the present study, we identified for the first time a mesenchymal progenitor cell population in the aortic valve using rigorous quantitative assays established in the mesenchymal stem cell field.…”
Section: Discussionmentioning
confidence: 99%
“…In quantitative terms, bone marrow-derived cells accounted for 20-30 % of fibroblasts in normal adult myocardial tissue [36,37,39]. In contrast, we found GFP+ label in myocytes at exceedingly low frequency [36] making this approach suitable for a targeted assessment of non-myocyte contributions to cardiac structure and function. It is important to recall, in this context, that not all lineage markers of hematopoietic cell sources (e.g., CD34) are applicable across species.…”
Section: Postnatal Origin Of Cardiac Fibroblastsmentioning
confidence: 75%
“…Recent single cell engraftment experiments indicate that in postnatal and adult life, cardiac fibroblasts are also derived from bone marrow or from pericytes that express the hematopoietic stem cell marker -CD45 [33][34][35][36][37][38]. In these experiments, adult mice were lethally irradiated and a single (or clone) of a rigorously isolated wild-type CD45+ hematopoietic stem cell (HSC) carrying a green fluorescent protein (GFP) marker was injected into their tail vein.…”
Section: Postnatal Origin Of Cardiac Fibroblastsmentioning
confidence: 99%
See 2 more Smart Citations